2015
DOI: 10.1186/s12889-016-2785-7
|View full text |Cite
|
Sign up to set email alerts
|

Trends in childhood pneumococcal vaccine coverage in Shanghai, China, 2005–2011: a retrospective cohort study

Abstract: BackgroundIn China, the pneumococcal conjugate vaccine (PCV7) and the pneumococcal polysaccharide vaccine (PPSV23) are not offered under the government’s Expanded Program on Immunization and are instead administered for a fee. PCV7 is more effective and covers more serotypes associated with invasive disease in children, but is also more expensive, than PPSV23. Because of their expense, there is concern that these vaccines, especially PCV7, have low uptake particularly among non-locals, migrants from outside of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…According to a survey of children age 1 to 2 years selected from 31 provinces throughout China conducted in 2012, 9.9% of children had received one dose of PCV7 [ 49 ]. Another study from Shanghai reported a similar PCV7 coverage level at 11.4% [ 55 ]. We observed a slightly change of PCV7 coverage level from 43.9% (34.1, 53.6%) to 52.1% (37.3, 66.9%) between pre/post vaccination period because of the limited herd immunity from low vaccine rate of pneumococcal conjugate vaccination.…”
Section: Discussionmentioning
confidence: 85%
“…According to a survey of children age 1 to 2 years selected from 31 provinces throughout China conducted in 2012, 9.9% of children had received one dose of PCV7 [ 49 ]. Another study from Shanghai reported a similar PCV7 coverage level at 11.4% [ 55 ]. We observed a slightly change of PCV7 coverage level from 43.9% (34.1, 53.6%) to 52.1% (37.3, 66.9%) between pre/post vaccination period because of the limited herd immunity from low vaccine rate of pneumococcal conjugate vaccination.…”
Section: Discussionmentioning
confidence: 85%
“…S. pneumoniae was detected in 3% of the study population, which is similar with a recent study in USA (4%) [ 6 ], but lower than an earlier US pediatric pneumonia etiology study. The 7-valent pneumococcal conjugate vaccine was introduced to China in 2008, it has been covered in around 15% of the children in the last seven years [ 14 ]. While our data, as well as the recent study in USA [ 6 ], partly reflect the substantial reduction of pneumococcal disease due to conjugate vaccines, bacterial culture-based diagnostics have limited sensitivity and bacteremia is detected in a minority of pneumococcal pneumonias [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the average vaccine coverage of PCV7 (37.5%) and PCV13 (58.3%) in the population was similar to the vaccine coverage before they were introduced into China [ 28 ], suggesting that the effects of PCV7 and PCV13 in China were limited. Exclusion from the national immunization program and high prices could be responsible for low vaccination rates and poor herd immunity in the target population [ 29 ]. We also found that in areas with better economic development, vaccine coverage was lower than in less economically developed regions.…”
Section: Discussionmentioning
confidence: 99%